Linguistic Understanding of the Categories of Space and Time - Oripovna, Shukurova Nigina (International Journal on Integrated Education, 2023)
In connection with the increased interest in text analysis in the context of the cognitive approach, for many scientists, the problem of identifying categories that can structure and convey a systemic idea of ​​linguistic units that have subject, conceptual or functional similarity of the designated phenomena becomes relevant. Such categories are "space" and "time", acting as universal concepts in the system of universal knowledge.